MILLENNIAL-SCALE VARIABILITY OF HOLOCENE HYDROGRAPHY IN THE SOUTHWESTERN OKHOTSK SEA: DIATOM EVIDENCE - Shimada C.; Ikehara K.; Tanimura Y.; Hasegawa S. (My University, 2004)
Diatom analysis of two submarine cores off eastern Hokkaido Island, northern Japan, provides insights into the Holocene palaeoenvironmental history of the southwestern Okhotsk Sea. Diatom flora was mainly composed of open-water and/or high-productivity-related Thalassionema nitzschioides, Neodenticula seminae and sea-ice-related species such as Bacterosira fragilis and Fragilariopsis cylindrus, suggesting millennial-scale alternation of dominant hydrographic regimes. Great abundances of T. nitzschioides and N. seminae, in particular, together with the ice-related species, from the early Holocene onward show that this biota was the major contributor to productivity in the southwestern Okhotsk Sea. On the other hand, faint but important occurrences of warm-water species such as Fragilariopsis doliolus were observed during 6.3-5.5, 4.2-2.7 and 1.1-0.2 ka. Such rhythmic occurrences of warm-water species as a sensitive indicator of the Soya Warm Current and the terminal branch of the subtropical Kuroshio Current reflect this history. The presence of this warm species is probably in tune with pulses of the Tsushima Warm Current that have been documented in Holocene sediments of the Japan Sea. These floral results, which might imply the millennially paced variability in palaeoclimate regimes in both Subarctic and subtropical regions, are well documented in these cores from the southwestern Okhotsk Sea.
Keywords: Diatom; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен